2018
DOI: 10.1002/hed.25503
|View full text |Cite
|
Sign up to set email alerts
|

Values of fine‐needle aspiration cytology of parotid gland tumors: A review of 996 cases at a single institution

Abstract: Background We evaluated the diagnostic accuracy of fine‐needle aspiration cytology (FNAC) in a large series of benign and malignant parotid tumors. Methods The FNAC diagnosis of 821 benign and 175 malignant parotid tumors managed at our department between 1999 and 2017 was correlated with the final histology. Results FNAC made a correct histopathological diagnosis in 72% of the benign parotid tumors; however, FNAC provided a correct grade in only 34% of the malignant tumors. FNAC correctly identified the histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 15 publications
4
25
2
Order By: Relevance
“…We found previously that 10% of submandibular gland tumors with a benign cytology turned out malignant, 20 and Suzuki et al 14 showed this risk to be even 14% in parotid tumors. Thus, a risk for malignancy remains: in our series, one such tumor turned out to be carcinoma ex PA.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…We found previously that 10% of submandibular gland tumors with a benign cytology turned out malignant, 20 and Suzuki et al 14 showed this risk to be even 14% in parotid tumors. Thus, a risk for malignancy remains: in our series, one such tumor turned out to be carcinoma ex PA.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, 36% were Warthin tumors, which is significantly more than in other series (8%-15%), 15,17 but reflects figures presented by Perkins et al 18 Most malignant tumors in our study were SDCs (31%), a significantly differing finding from other studies where other tumor types predominate. 13,14,16,19 We encountered no adenoid cystic carcinomas (ACC), but noteworthy, the overall number of malignancies remained low. In our previous study of submandibular gland neoplasms, ACC was the most common type of malignancy.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations